Pedagogic and Managerial Competence for School Principals or Leaders in Early Childhood Education Management - Abednego Abednego; Patris Rahabav (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The research aims to have a significant influence on the synergy model of pedagogical competence and managerial competence on PAUD management training. This type of research is quantitative using True Experimental Design with Pretest-Posttest Only Control Design. The experimental group was a group with a synergy of pedagogical competence and managerial competence, while the control group was a group that used a conventional training model, each group consisting of 21 managers. Data were analyzed using the N-Gain Test and T-Test. The research results revealed 1) The average N-Gain score for the experimental group was 89.38% (Effective) compared to the average N-Gain score for the control group, namely 75.57% (Quite Effective). 2) The results of the Paired Sample T-Test show a significant influence on increasing learning outcomes for school principal training in early childhood management. The synergy of pedagogical competence and managerial competence is recommended to be implemented in various training programs for school principals and leaders for PAUD management